PERFORMANCE OF ISA BROWN CHICKEN AGED 99-103 WEEK GIVEN COMMERCIAL RATION WITH SEASHELL FLOUR SUPPLEMENTATION - F. A., Febryanti; Dewi, G. A. M. K.; Mahardika, I G. (Jurnal Peternakan Tropika, 2020)
This study aims to determine the performance of Isa Brown chicken aged 99-103 weeks who were given a commercial ration with seashell flour supplementation. The Research held in Pesedahan Village, Manggis District, Karangasem, Bali. The design used was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, and each replication used 5 chickens. The treatment given is; layer chickens were given commercial rations without additional seashell flour (A), chickens were given commercial rations and 1% seashell flour (B), chickens were given commercial rations and 2% seashell flour (C), chickens were given commercial rations and 3% seashell flour (D). The variables observed were feed consumption, hen-day production , egg weight, feed conversion and Income Over Feed Cost (IOFC). The results of this study indicate that the administration of 1%, 2%, and 3% shellfish flour in commercial rations gives results that have no significant effect (P> 0.05) on ration consumption, ration consumption, hen-day production , egg weight, conversion ration but out can increased the Income Over Feed Cost (IOFC ) compared to control treatment (A). Based on the results of this study it can be concluded that the administration of seashell flour by 1%, 2%, and 3% gives the same results on ration consumption, hen-day production, egg weight and ration conversion but can increase the Income Over Feed Cost.   Keywords: performance, Isa Brown, seashell flour